Monitoring of circulating amino acids in patients with pancreatic cancer and cancer cachexia using capillary electrophoresis and contactless conductivity detection - Tůma, Petr; Hložek, Tomáš; Kamišová, Jana; Gojda, Jan (Electrophoresis, 2021)
Branched chain amino acids (BCAAs), alanine and glutamine are determined in human plasma by capillary electrophoresis with contactless conductivity detection (CE/C4D). The baseline separation of five amino acids from other plasma components is achieved on the short capillary effective length of 18 cm in 3.2 mol/L acetic acid with addition of 13% v/v methanol as background electrolyte. Migration times range from 2.01 min for valine to 2.84 min for glutamine, and LODs for untreated plasma are in the interval 0.7–0.9 μmol/L. Sample treatment is based on the addition of acetonitrile to only 15 μL of plasma and supernatant is directly subjected to CE/C4D. Circulating amino acids are measured in patients with pancreatic cancer and cancer cachexia during oral glucose tolerance test. It is shown that patients with pancreatic cancer and cancer cachexia syndrome exhibit low basal circulating BCAAs and glutamine levels and loss of their insulin‐dependent suppression.